Institutional Readiness and Stakeholder Demand for a Doctor of Philosophy in Science Education - Elreen Aguilar-Delavin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This feasibility study examined the proposed offering of a Doctor of Philosophy in Science Education at the Graduate School of Dr. Emilio B. Espinosa Sr. Memorial State College of Agriculture and Technology in Masbate, Philippines. Data were gathered through a researcher-developed questionnaire with demographic items, Likert-scale indicators, and open-ended questions. Quantitative responses were summarized using frequencies, percentages, and weighted means, while the written comments were grouped through thematic analysis. Stakeholders generally viewed the proposed program favorably. The strongest ratings concerned its relevance to current educational needs, the breadth of the curriculum, the preparation of graduates for academic and research careers, and the expected contribution of the program to science education. Lower ratings were recorded for opportunities to present at national and international conferences (M = 3.65), faculty-student research collaboration (M = 3.90), scholarships or assistantships (M = 4.15), and regular curriculum updating (M = 4.15). These findings suggest that the program is attractive to its intended market, but still requires deliberate investment in research culture, student support, and academic networking. The financial projection remains positive under the stated enrollment and tuition assumptions, with a corrected six-year cumulative net balance of PHP 914,700. The program is feasible in principle, provided that DEBESMSCAT verifies the respondent dataset, documents instrument validity and reliability, secures regulatory approval, and confirms that faculty, laboratories, research resources, and long-term financing are adequate.